Leksykalne zapożyczenia rosyjskie w „Tygodniku Ilustrowanym” z lat 1926–1930 - Joachimiak-Prażanowska, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The present article is a contribution to the study of the history of Polish-Russian linguistic contacts and focuses on the phenomenon of Russianisms (Russian expressions) in the Polish language, in particular on the phenomenon of lingering Russianisms in the Polish language during the inter-war period (1918–1939). The issue has not been sufficiently and thoroughly scholarly addressed so far. The article discusses the lexical borrowings from Russian that were used in the Polish language used in “Tygodnik Ilustrowany”. This weekly publication was published in Warsaw throughout the whole of the inter-war period in Poland. The analysis covers relevant vocabulary excerpted from five annual volumes of the periodical, i.e. from the years 1926–1930. The author attempts to prove and illustrate to what degree the influence of the Russian language was manifested in the lexis used by editors and journalists of the weekly, what elements of this influence remained between 1918–1939 after the long period of partition and the immense influence of Russian upon the Polish language. Additionally, the author examines whether the Russian influences gained support in the Polish language of former inhabitants of the Eastern Polish borderlands who later settled in free Warsaw or in the language of those of its inhabitants who spent part of their lives in Russia.